PRAKTEK AKUNTABILITAS DAN KOMPETENSI SUMBER DAYA MANUSIA UNTUK PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA - Komang Adi Kurniawan Saputra; Putu Dian Pradnyanitasari; Ni Made Intan Priliandani; I Gst. B. Ngr. P. Putra (KRISNA: Kumpulan Riset Akuntansi, 2019)
This study aims to examine the effect of accountability and competency of human resources on fraud prevention processes in the management of village funds in the Province of Bali. The research design used is quantitative with the survey method. The study sample was determined with the help of Slovin formula with a total of 88 official villages in the Province of Bali that received village funding assistance. Data from the answers to questionnaires from respondents were tested by multiple linear regression analysis and resulted that the variables of accountability and competence of human resources had a positive influence on the prevention of fraud in village fund management.